In Vitro Evaluation of Purple Sweet Potato Leaf Extract (Ipomoea batatas) as a Tyrosinase Inhibitor and Malondialdehyde Formation Inhibitor - Purnamasari, Dewi; Safithri, Mega; Andrianto, Dimas (Universitas Djuanda, 2024)
The study purple sweet potato is known to contain flavonoids, a class of natural polyphenols with the capability to mitigate skin pigmentation. The research aims to assess the antioxidant and tyrosinase inhibitory activities of purple sweet potato extracts obtained through hexane, ethyl acetate, ethanol, and water solvents. The results of phytochemical identification show that the extract contains various secondary metabolites which have the potential to act as antioxidants. The DPPH method IC50 values of 6948.12ppm for n-hexane, 3015.19ppm for ethyl acetate, 128.05ppm for ethanol, and 791.77ppm for water extract. The MDA inhibitor test IC50 values of 2067.02ppm for n-hexane, 1968.13ppm for ethyl acetate, 116.14ppm for ethanol, and 921.14ppm for water extract. In the tyrosinase inhibitor assay, IC50 values were 1328.29ppm for n-hexane, 1245.13ppm for ethyl acetate, 217.35ppm for ethanol, and 391.21ppm for water extract. Tuckey test statistics, ethanol extract was not significantly different from the positive control in the DPPH test, MDA inhibitor and tyrosinase test. These findings suggest that purple sweet potato extracts, particularly the ethanol extract, hold promise as natural ingredients with antioxidant and tyrosinase inhibitory properties, making them potential candidates for safe and effective skin brightening formulations.